Study on friction and wear properties of nickel-based alloys under different working conditions - Ming Li; Yongjun Bai; Yi Ou; Xiaoyu Ren; Chaoqun Qian (Heliyon)
This study systematically analyzes the friction and wear properties, as well as the fatigue life characteristics, of high-hardness nickel-based alloys under specialized working conditions. The primary contribution lies in elucidating the frictional behavior and wear mechanisms of these alloys under varying rotational speeds, loads, and lubrication environments, while establishing S-N curves specifically tailored to nickel-based alloys. These findings provide theoretical support for optimizing their engineering applications in extreme environments. Friction and wear tests are conducted using a Bruker UMT Tribolab wear testing machine to examine surface wear morphology. A white-light interferometer is employed to measure wear profiles and calculate wear rates, while a fatigue testing machine collects stress-life data to model S-N curves. Experimental results show that increasing rotational speed slightly raises the average coefficient of friction, with adhesion on the material surface positively correlated to speed. The wear rate initially decreases and then increases with higher rotational speeds. Under increasing load, the fluctuation amplitude of the friction coefficient diminishes and stabilizes, accompanied by a gradual decline in its average value. The furrow phenomenon on the surface correlates positively with load, and while the wear rate decreases with increasing load, the rate of decrease slows over time. The formation of a lubricating film contributes to the uniform distribution of the load, and a positive correlation is observed between the wear rate and the coefficient of friction. Fitting results of the S-N curve reveal that the fatigue life of nickel-based alloys adheres closely to an exponential function relationship. This study offers critical theoretical insights to support the design and application of nickel-based alloys in extreme conditions, such as those encountered in nuclear power systems.